The Effect of Folic Acid IntakeAgainst IUGR in Pregnant Mothers Trimester I - Feva Tridiyawati; Afia Mulyaningsih (CV. Inara, 2022)
Nutritional problems are currently the most important because they are a direct cause of death experienced by mothers and their babies after childbirth. Dominantly low nutritional intake and related to poor nutritional status in pregnant women during pregnancy will cause various good impacts on both mother and baby, for example, low birth weight. Bay has been born into this world with a baby weight of more than 2,500 grams. Growth retardation in the fetus is known as intrauterine growth restriction (IUGR). This study aims to determine the effect of giving polalic acid to women who are pregnant in the first trimester and its effect on IUGR. The research was conducted using Google Scholar with the variables studied. The article/review is then read and internalized according to the written criteria and then used as a literature review. The results of the study were carried out by taking articles using observational analysis research methods using cross sectional research methods with a duration of less than 5 years (2016-2021). There is an effect of IUGR on folic acid intake in first trimester pregnant women. deficiency in folic acid during pregnancy and can occur and cause risk factors for fetal malformations and the development of placental disease. A sign of folic acid deficiency is anemia caused by abnormal production of red blood cells. Adequacy of folic acid for pregnant women is 600 g / day to 800 g / day. Folic acid can be obtained from fresh green leafy vegetables, oranges, potatoes and whole grains.